An examination of how and why triathlon coaches use a suite of technologies in their practice - Wells, L.; Konoval, T.; Bruce, L. (International Journal of Sports Science & Coaching, 2023)
Current literature has examined the technical aspects of triathlon, technologies used in triathlon, and coaching practice in isolation. However, what is not known, and what this research will examine for the first time, are the relationship between these elements and how they interconnect and influence each other. The study also examines how coaches decide what technology to use and why, in relation to their coaching philosophy. Seven individual 1-hour interviews were conducted via video conference with national and international triathlon coaches. The coaches (n = 7) had varying backgrounds, including former elite-level athletes, sport science professionals, and health science graduates. Using a qualitative inductive and deductive thematic analysis, four central themes were discovered. Findings indicate that the opportunities and challenges of implementing new and emerging technologies are ongoing, with coaches not always having consistent views, levels of flexibility, or open-mindedness as to which technologies to use and why. Notably, coaches are concerned about athletes' over-reliance on technology and the data it produces, impacting the athlete's perception of their effort. We conclude that despite switching between different philosophical views of technology, coaches ultimately choose a suite of technologies based on comfort in addition to selecting tools that will enhance the performance of their athletes. Coaches also prioritise the health and well-being of their athletes and will use technology to assist in collecting data to aid in this process. Finally, coaches want athletes to stay `in tune` with their inner sense of effort, and not become overly reliant on objective data.